Pengaruh Motivasi Dan Kepuasan Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Tiki Jalur Nugraha Ekakurir (JNE) Di Wilayah Pedati Jakarta Timur - Dikdoyo, Aji; Amalia, Dini; Ramadhoni, Achmad (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The purpose of this study was to determine the effect of motivation and job satisfaction onemployee performance at PT. Tiki JNE carriage in East Jakarta. This research wasconducted using data collection methods by distributing questionnaires to 110 employees ofPT. Tiki JNE Pedati East Jakarta. Samples were taken using the slovin formula. The analysisused in this study is data quality testing consisting of validity and reliability tests, which arethen tested structural models by looking at the R-Square value and the resulting Q-squarevalue, and finally testing the hypothesis by looking at the T-statistics value and the value Theresulting P Value.The results showed that work motivation had a direct significant effect on job performance,and job satisfaction had a direct significant effect on job performance.